Modelling the monetary policy transmission on the manufacturing output: Evidence from the fastest growing Indian economy. Issue 3 (23rd September 2020) - Sankaran, Arumugam; K, Arjun; Vadivel, Arjunan
Abstract : The existing literature portrays that the instruments of monetary policy, such as interest rate, money supply, and price have a direct bearing on economic growth and social welfare. Against this background, the present study investigates the monetary policy transmission on manufacturing output in one of the fastest‐growing economies—India. Highlighting how the Central Bank works in a political–economic context, the precise research question used entails—how does monetary policy affect the manufacturing output in India? And what is the transmission channel and level of magnitude? To address these questions, we employed autoregressive distributed lag bounds testing for co‐integration on the time series data collected from World Development Indicators and International Finance Statistics for the period from 1980 to 2018. The model estimation affirms the presence of a co‐integrating relationship among the variables. In the short run, we have a mixed result of relationship among determining variables and manufacturing output, while in the long run, the lending rate has positive and the exchange rate has significant relationships among the variables. The variables such as consumption and gross capital formation have insignificant influence even though negative. The causality test reveals unidirectional short‐run causality stemming from lending rate to industrial output testifying lending rate‐driven growth. In a nutshell, the lending rate has long‐term positive relationship with that of industrial output, and the functional independence of the Central Bank has long‐term consequences on output and this requires a right chord of balance to be struck between political motives and the RBI's autonomy.